(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The vital functions of a multicellular organism are carried out with the assistance of its constituent cells, tissues, and organs, integrated into systems through dynamic interactions with the environment during the exchange of substances, energy, and information. In this regard, in accordance with the traditions of Russian physiology, formulated in the mid-19th century by I.M. Sechenov: " the scientific definition of an organism must also include the environment that influences it." Moreover, in accordance with the concepts of the theories of V.I. Vernadsky and A.L.I. Chizhevsky, it is not simply the state of the external environment, but specifically its dynamics, that determines the anticipatory tendencies in the organism’s activity. It is generally accepted that the anticipatory reflection of reality, as an attribute of living systems, arose due to the fact that the temporal structure of reality is represented by repeating series of events. From this perspective, the activity of an organism during a certain period of time reflects anticipatory preparation for upcoming activity. Fluctuations in the state of the organism and the functioning of its systems occur under the influence of the dynamics of environmental conditions and during the course of activity. Factors affecting the body, depending on the type of reaction, are classified as episodic (acute, sudden) and periodic (chronic). In response to sudden stimuli, the body responds with a nonspecific reaction, which, depending on the strength of the stimulus, represents a tension reaction (stress), activation, or training. The body reacts to repeated stimuli according to the principle of anticipatory reflection of reality. Natural and man-made environmental conditions are represented by abiotic and biotic factors. Perception of changes in abiotic factors is ensured through sensory systems, and biotic factors are perceived through the immune system. Moreover, abiotic factors directly influence the central links of neural and neuroendocrine regulation, and the effect of biotic factors on regulatory mechanisms is mediated by the state of the effector and secretory functions of immune system cells. It is known that various leukocyte populations, in response to antigens, secrete cytokines and mediators that influence the state of the central structures of autonomic and neural regulation.